What is life? There are more than 100 answers to this basic question - Monge-Nájera, Julián (2022)
Like the COVID viruses that inspired this image, the Mona Lisa is not alive, but, 500 years ago, the substrate of the Mona Lisa was a living thing, a beautiful tree growing in northern Italy. When did it stop fitting the definition of life? What is life? Where is the border between the living and the inert?